Competition between pinning produced by extrinsic random point disorder and superconducting thermal fluctuations in oxygen-deficient GdBa2Cu3O x coated conductors - Haberkorn, N. (2019)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina